The ability of the Arctic isolate of Trichinella nativa to adapt to laboratory animals - L. A. Bukina (Российский паразитологический журнал, 2016)
It has been established that the Arctic isolate of Trichinella spp. not adapted to laboratory animals, although this strain is adapted to Syrian hamsters and gerbils. The European isolate of Trichinella spp. was found to be infective for laboratory animals, rodents and carnivores living on the Chukotka Peninsula.